Low-temperature, solution-deposited metal chalcogenide films as highly efficient counter electrodes for sensitized solar cells1. Issue 12 (28th March 2015) - Liu, Feng; Zhu, Jun; Hu, Linhua; Zhang, Bing; Yao, Jianxi; Nazeeruddin, Md. K.; Grätzel, Michael; Dai, Songyuan
<x xml:space="preserve">Abstract</x> Solution-deposited chalcogenide films show better catalytic performance than platinum-loaded electrodes in both iodide/triiodide (FeSe2) and polysulfide (Cu1.8S and CuSe) redox systems.